2022
DOI: 10.3389/fnmol.2022.893083
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Exposure Induces Neurocognitive Impairments and Neuropathological Changes in the Hippocampus

Abstract: Background and ObjectiveNeurocognitive dysfunction is present in up to ∼61% of people with chronic obstructive pulmonary disease (COPD), with symptoms including learning and memory deficiencies, negatively impacting the quality of life of these individuals. As the mechanisms responsible for neurocognitive deficits in COPD remain unknown, we explored whether chronic cigarette smoke (CS) exposure causes neurocognitive dysfunction in mice and whether this is associated with neuroinflammation and an altered neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…We have also shown that chronic cigarette smoke exposure induces a reactive astrocyte profile within the hippocampus (Dobric et al, 2022) and hypothalamus (De Luca et al, 2023). This reactive astrocyte profile was associated with endothelial cell tight junction protein impairment (reduction in ZO-1), thus reducing BBB integrity, compared to sham mice, leading to working memory impairments (Dobric et al, 2022).…”
Section: Senescence-associated Secretory Phenotypementioning
confidence: 76%
“…We have also shown that chronic cigarette smoke exposure induces a reactive astrocyte profile within the hippocampus (Dobric et al, 2022) and hypothalamus (De Luca et al, 2023). This reactive astrocyte profile was associated with endothelial cell tight junction protein impairment (reduction in ZO-1), thus reducing BBB integrity, compared to sham mice, leading to working memory impairments (Dobric et al, 2022).…”
Section: Senescence-associated Secretory Phenotypementioning
confidence: 76%
“…The Sham mice were handled identically and exposed to room air. We have previously shown that this cigarette smoke exposure protocol in male BALB/c mice recapitulates key clinical traits of human COPD, including lung inflammation and pathology (airway inflammation, emphysema and impaired lung function), increased lung and systemic oxidative stress and co-morbidities including skeletal muscle dysfunction (Chan et al, 2020;Dobric et al, 2022). Hence, only male mice were included in the present study.…”
Section: Cigarette Smoke Exposurementioning
confidence: 99%
“…The Sham mice were handled identically and exposed to room air. We have previously shown that this CS exposure protocol in male BALB/c mice recapitulates key clinical traits of human COPD, including lung inflammation and pathology (airway inflammation, emphysema and impaired lung function), increased lung and systemic oxidative stress and comorbidities including skeletal muscle dysfunction (Chan et al, 2020;Dobric et al, 2022). Hence, only male mice were included in the present study.…”
Section: Cigarette Smoke Exposurementioning
confidence: 99%
“…Fat and lean contents were determined using an EchoMRI apparatus (Echo Medical Systems, Houston, TX, USA). To understand the systemic impact of CS exposure and apocynin treatment, whole blood was collected from the inferior vena cava at the end of the experiment and counted using a CELL-DYN Emerald hematology analyser (Abbott Core Laboratory, USA), as previously described (Dobric et al, 2022).…”
Section: Body Composition Scan and Blood Analysismentioning
confidence: 99%
See 1 more Smart Citation